2021
DOI: 10.1007/s42991-021-00163-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects on carrion consumption in a mammalian scavenger community when dominant species are excluded

Abstract: Carrion is a valuable resource exploited not only by obligate scavengers but also by a wide variety of facultative scavengers. These species provide several important ecosystem services which can suffer if the scavenger community composition is altered, thus reducing the ecosystem provided. We studied the response of the Mediterranean facultative scavenger community to the exclusion of larger scavenger species (red fox Vulpes vulpes, European badger Meles meles, and wild boar Sus scrofa) using an exclusion fen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…In the context of agroecosystems, wild boar feed on a rich community of animal species (including game and livestock species). Wild boar consume carrion (Inagaki et al 2020;Tobajas et al 2021a), although the overall relative proportion of scavenged vs. preyed-upon vertebrate foods is frequently unknown (Taylor and Hellgren 1997) because it is often impossible to know whether an animal was killed deliberately or ingested as carrion (Wilcox and Van Vuren 2009). Therefore, facultative scavengers such as wild boar are expected to have no direct effect on taxa they consume as carrion, although they will have a direct negative impact on prey taxa that they consume via predation (Wilson and Wolkovich 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of agroecosystems, wild boar feed on a rich community of animal species (including game and livestock species). Wild boar consume carrion (Inagaki et al 2020;Tobajas et al 2021a), although the overall relative proportion of scavenged vs. preyed-upon vertebrate foods is frequently unknown (Taylor and Hellgren 1997) because it is often impossible to know whether an animal was killed deliberately or ingested as carrion (Wilcox and Van Vuren 2009). Therefore, facultative scavengers such as wild boar are expected to have no direct effect on taxa they consume as carrion, although they will have a direct negative impact on prey taxa that they consume via predation (Wilson and Wolkovich 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of factors that drive the consumption of small game species in agroecosystems (e.g. hunting, densities) is mostly unknown (Wilcox and Van Vuren 2009;Tobajas et al 2021aTobajas et al , 2021b.…”
Section: Introductionmentioning
confidence: 99%
“…For example, wildlife may become infected because of livestock, domestic animals or human wastes, or there may be transmission between wild animals [ 28 , 29 ]. In this framework, wild carnivores may have a crucial role in spreading Salmonella in the environment or getting infected due to their nutrition habits as scavengers or predators [ 30 , 31 ]. The current study showed the presence of different Salmonella subspecies and serotypes in wild mammalian carnivores from the Emilia-Romagna Region between 2016 and 2022.…”
Section: Discussionmentioning
confidence: 99%
“…3), which is similar or shorter than the period in which baits are usually applied for population control, vaccination or in CFA with foxes (Steelman et al 2000;Tobajas et al 2021a). However, the persistence time and the effectivity of bait intake could vary depending on the ecosystem and the predator assemblages (Tobajas et al 2021b). Studies using baits to control the populations of red foxes and cats in Australia have reported highly variable rates of bait intake (0-70%) and often lower than 20% (Algar et al 2007;Moseby et al 2009;, depending on several characteristics such as bait placement, type of bait, aversion to consuming unfamiliar foods, weather, target and non-target species abundance or alternative live prey availability (van Polanen Petel et al 2001;Algar et al 2007;.…”
Section: Discussionmentioning
confidence: 99%